Longitudinal analysis of student learning motivation from past experiences to future career projections - Anggayana, I Wayan Agus (Privietlab, 2026)
This study investigates the motivational trajectory of Indonesian college students, examining the dynamic shifts that occur from their foundational past experiences to their articulation of future career ambitions. Employing an interpretive qualitative design rooted in narrative inquiry, this study analyzed rich, in-depth interview data from 13 participants (N=13), focusing on their lived motivational experiences across three distinct temporal phases: past, present, and future. Interpreted through the integrated frameworks of Self-Determination Theory (SDT) and the L2 Motivational Self System (L2MSS), the findings document a critical psychological evolution. Initial motivation (the ought-to self) was characterized as controlled and extrinsic, primarily stemming from filial obligation and the intense desire for external familial validation, such as